Comparative efficacy and safety of intravenous and oral administration of a TRH analogue (RX77368) in motor neuron disease. Issue 11 (November 1990) - Modarres-Sadeghi, H; Guiloff, R J
Abstract : Ten consecutive patients with motor neuron disease (MND) who had bulbar symptoms received one or two intravenous doses followed by increasing oral doses of a TRH analogue (RX77368). Similar improvements in speech, swallowing and in tongue and jaw movements were seen after iv and oral administration in nine, five and eight patients respectively. The initial time course of improvement correlated with increasing plasma levels of the drug, but most clinical effects persisted when the levels decreased and became undetectable after 24 hours. The oral solution was tasteless and had no, or minimal, side effects.